Cover Feature: Triplet–Triplet Annihilation Upconversion for Photocatalytic Hydrogen Evolution (Chem. Eur. J. 71/2019). Issue 71 (6th November 2019) - Yu, Tianjun; Liu, Yanpeng; Zeng, Yi; Chen, Jinping; Yang, Guoqiang; Li, Yi
Abstract : A red‐light‐driven photocatalytic hydrogen production system was constructed by combining TTA‐based upconversion micelles with semiconductor Cd0.5 Zn0.5 S. Micelles upconvert red photons to cyan photons, which were subsequently absorbed by Cd0.5 Zn0.5 S to reduce protons to hydrogen gas. This strategy is beneficial for the solar energy utilization efficiency of the artificial photocatalyst system by increasing the light‐harvesting capability of low energy photons. More information can be found in the Full Paper by T. Yu, Y. Li, et al. on page 16270 .